Examining the validity and reliability of e-lifestyles scale in the Malaysian context: Preliminary results - Ahmad, Norzieiriani; Omar, Azizah; Ramayah, T. (2012)
This study sought to construct and validate e-lifestyle scale that would capture for the online marketers a more holistic picture of people's lifestyles.Thus, the purpose of this study is to examine the goodness of measure (validity and reliability) of e-lifestyle scale based on Activities, Interests and Opinions (AIO).The respondents in this study are online shoppers who have purchased a product or service through online shopping.In this study, data collection was carried out via an online survey.Results of this study show that the 30 A10 items of the e-lifestyle scale were grouped into four distinct components.These components represented four principal factors that significantly influence and shape individual e-lifestyles. Findings of this study provide e-marketers with insights into how knowledge about lifestyle factors can be integrated into marketing and advertising strategies particularly in online shopping context.